The Effect of Flash Sales, Fear of Missing Out, and Hedonic Shopping Value on Impulse Buying of Beauty Products on The Shopee Marketplace (A Case Study of Shopee Users in Denpasar City) - Ni Kadek Indah Handayani; I Gusti Ayu Imbayani; I Made Surya Prayoga (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Rapid technological developments in the era of globalization have changed people's lifestyles, especially in communication and shopping, with the majority of Indonesians now preferring online shopping through marketplaces such as Shopee, which offer convenience, comfort, and high accessibility. This study aims to analyze the influence of flash sales, fear of missing out, and hedonic shopping value on impulse buying of beauty products on the Shopee marketplace (Case Study of Shopee Users in Denpasar City). A quantitative research design was used with a questionnaire distributed to 119 respondents who were active Shopee users in Denpasar City. Data were analyzed using multiple linear regression with IBM SPSS 25.0 software. The results of the analysis show that flash sales do not have a significant effect on impulse buying, meaning that flash sale programs do not directly encourage consumers to make unplanned purchases of beauty products on the Shopee marketplace. Fear of missing out has a positive and significant effect on impulse buying, meaning that the higher the fear of missing out, the more consumers' impulse buying behavior towards beauty products on the Shopee marketplace will increase. Hedonic shopping value has a positive and significant effect on impulse buying of beauty products on the Shopee marketplace, meaning that as hedonic shopping value increases, consumers' impulse buying behavior towards beauty products on the Shopee marketplace will also increase.